Audit Market Concentration: Some Evidence from the Republic of North Macedonia - Bozhinovska Lazarevska, Zorica; Dionisijev, Ivan; Tocev, Todor; Malchev, Bojan (Lex Localis, 2023)
Audit market concentration has been thoroughly researched both globally and regionally. According to previous studies, the audit market is often dominated by the Big Four at the EU level, while in the region, the concentration is lower, indicating that it has oligopolistic features. This paper analyzes and measures the concentration of the audit market in Republic of North Macedonia, through Herfindahl-Hirschman index - HHI and concentration ratio - CR4, based on three independent variables: auditrelated revenue, number of clients and number of employees. The research covers the period from 2014 to 2021 and it is concluded that at the beginning of the analyzed period (2014-2017), according to audit-related revenue, the audit market in Republic of North Macedonia had the characteristics of an oligopoly, but today it is nonconcentrated market and ranges from perfect competition to oligopoly. In terms of the number of employees and the number of clients, the results from our research show that audit market in Republic of North Macedonia is not concentrated.
Keywords: audit market; concentration; big four; audit firms; Republic of North Macedonia